2008
DOI: 10.1155/2008/275357
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of 4H-SiC Double Drift Region IMPATT Device as a Photo-Sensitive High-Power Source at 0.7 Terahertz Frequency Regime

Abstract: The dynamic performance of wide-bandgap 4H-SiC based double drift region (p ++ pnn ++ ) IMPATT diode is simulated for the first time at terahertz frequency (0.7 Terahertz) region. The simulation experiment establishes the potential of SiC based IMPATT diode as a high power (2.5 × 10 11 Wm −2 ) terahertz source. The parasitic series resistance in the device is found to reduce the RF power output by 10.7%. The effects of external radiation on the simulated diode are also studied. It is found that (i) the negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
3
7
0
Order By: Relevance
“…But some recent theoretical study reveals the potentiality of InP-based IMPATTs as THz sources . In recent years the potentiality of wide bandgap materials (SiC, GaN) for generation of RF power at THz frequencies has been reported Mukherjee et al 2009;Panda et al 2007Panda et al , 2001; Banerjee et al 2010). Yuan et al (2001) first demonstrated the 4H-SiC based p ?…”
Section: Introductionmentioning
confidence: 99%
“…But some recent theoretical study reveals the potentiality of InP-based IMPATTs as THz sources . In recent years the potentiality of wide bandgap materials (SiC, GaN) for generation of RF power at THz frequencies has been reported Mukherjee et al 2009;Panda et al 2007Panda et al , 2001; Banerjee et al 2010). Yuan et al (2001) first demonstrated the 4H-SiC based p ?…”
Section: Introductionmentioning
confidence: 99%
“…For an ideal read diode, according to Gilden and Hines [21], f a is given by where J 0 is the bias current density, α′ = d α / dE , α = α n = α P , and v S = v ns = v ps . However, the computer program adopted in the present analysis [5, 6, 9], for modeling and analyzing the small-signal behavior of high-frequency IMPATT devices, is free from such simplifying assumptions as done by Gilden and Hines [21]. In the present generalized simulation technique [9], α n ≠ α P , v ns ≠ v ps , and the value of f a at any J 0 is obtained from the admittance plot of the diode corresponds to the frequency at which B changes its sign from negative to positive.…”
Section: Computer Simulation Methodologiesmentioning
confidence: 99%
“…To achieve this the author developed a simulation program using an algorithmic flowchart based on different wellknown research works [4][5][6][7][8][9][12][13][14][15][16][17] as well as properly preserving all boundary conditions and properties of the device with adequate range of operation using MATLAB software. Here the author is able to set the ranges of various parameters independently according to requirement of the program, which in turn enhances the calibration of the program.…”
Section: Theory and Simulation Techniquementioning
confidence: 99%
“…Thus the method of optical tuning by illuminating the junction of the diode is one of the latest state-of-the-art technologies. Different theoretical and a few experimental studies in the last few years [4][5][6][7][8][9][10][11] showed the influence of optical control over normal electronic control of the DDR IMPATT device, and its application in optoelectronic integrated circuits and phased array antennas for space-based communication, imaging and advanced radars etc makes the methodology more interesting. The optical radiation consists of photons (hν) with higher value of energy when incident through optical window at the junction and interacting with semiconductor material (E g ), then it is absorbed (as hν > E g ) at either edges of p + or n + side of DDR IMPATT structure.…”
Section: Introductionmentioning
confidence: 99%